Praktik Jual Beli Buah Rusak Perspektif Hukum Ekonomi Syariah Pada Pasar Tradisional Seruway - Nisa, Afratun; Asnita, Dessy; Faisal, Faisal; Mudrika, Syarifah (IAIN Langsa, 2024)
The practice of buying and selling damaged fruits in the traditional market of Seruway Sub-district has been ongoing for a long time. In this practice, sellers offer these damaged fruits at relatively low prices, making them highly sought after by consumers. This writing aims to explore how the buying and selling of damaged fruits occur in the traditional market of Seruway Sub-district, Aceh Tamiang Regency, and how Islamic economic perspectives view such practices. The research employed a field research approach with a qualitative descriptive analysis method. The research findings conclude that the buying and selling of damaged fruits occur willingly between sellers and buyers. Sellers proactively separate good-quality fruits from damaged ones, allowing buyers to decide whether they are willing to proceed with the transaction. This approach minimizes disputes or deception between sellers and buyers. According to Islamic economic theory, the practice of buying and selling damaged fruits in the Seruway Sub-district Traditional Market is deemed legitimate. This is because it adheres to the requirements and principles of Islamic commerce. The study contributes to a better understanding of the legal status of buying and selling damaged fruits and can serve as a reference for further research on similar themes.